2018
DOI: 10.1111/jth.14017
|View full text |Cite
|
Sign up to set email alerts
|

Use of direct oral anticoagulants in antiphospholipid syndrome

Abstract: The direct oral anticoagulants (DOACs) are therapeutic alternatives to warfarin and other vitamin K antagonists (VKAs), and constitute the standard of care for many indications. VKAs constitute the conventional therapy for the treatment and secondary thromboprophylaxis of thrombotic antiphospholipid syndrome (APS), but are often problematic, owing to the variable sensitivity of thromboplastins to lupus anticoagulant. Thus, the International Normalized Ratio may not accurately reflect anticoagulation intensity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 94 publications
(141 reference statements)
1
50
0
2
Order By: Relevance
“…6,76 More recently, non-vitamin K antagonist oral anticoagulants (NOAC) have been investigated in patients with APS with divergent results. 77 Following the results from the Trial on Rivaroxaban in AntiPhospholipid Syndrome (TRAPS), 78 which included triple positive thrombotic APS, rivaroxaban is contraindicated in APS patients with triple aPL positivity. 72 An analysis from the RE-COVER/RE-COVER II and RE-MEDY trials showed similar safety and efficacy of dabigatran in patients with thrombophilia and previous venous thromboembolic events, in whom APS represented the second most common inherited disorders, accounting for 20% of all patients.…”
Section: Secondary Antiphospholipid Syndromementioning
confidence: 99%
“…6,76 More recently, non-vitamin K antagonist oral anticoagulants (NOAC) have been investigated in patients with APS with divergent results. 77 Following the results from the Trial on Rivaroxaban in AntiPhospholipid Syndrome (TRAPS), 78 which included triple positive thrombotic APS, rivaroxaban is contraindicated in APS patients with triple aPL positivity. 72 An analysis from the RE-COVER/RE-COVER II and RE-MEDY trials showed similar safety and efficacy of dabigatran in patients with thrombophilia and previous venous thromboembolic events, in whom APS represented the second most common inherited disorders, accounting for 20% of all patients.…”
Section: Secondary Antiphospholipid Syndromementioning
confidence: 99%
“…Some patients are investigated for haemostatic defects while on these drugs, but the interference in the assays can cause problems with interpretation and there is a significant risk that results can be misinterpreted . Of particular concern would be the potential for a misdiagnosis of acquired haemophilia A in patients with an apparent reduction in factor VIII activity and an apparent factor VIII inhibitor, or the potential for a misdiagnosis of antiphospholipid syndrome in patients with a falsely elevated lupus anticoagulant assay; this may effect patient treatment choices …”
Section: Introductionmentioning
confidence: 99%
“…an apparent reduction in factor VIII activity and an apparent factor VIII inhibitor, 3 or the potential for a misdiagnosis of antiphospholipid syndrome in patients with a falsely elevated lupus anticoagulant assay; 3,[5][6][7] this may effect patient treatment choices. 8 The recommended method for measuring direct anti-Xa anticoagulants is by LC-MS/MS or a suitably calibrated anti-Xa activity assay; 3 although this will identify patients whose results may be affected by these DOACs, it does not aid interpretation of the results of those assays.…”
mentioning
confidence: 99%
“…The British Society for Haematology (BSH) guidelines recommend that, due to lack of strong evidence, anticoagulation with warfarin should be considered in patients <50 years with stroke and APS using a target INR of 2·5 (2·0–3·0), but that there is no strong evidence to recommend it over antiplatelet therapy. Standard practice is to maintain a target INR of 2·5, with escalation to a higher target INR should thrombosis recur (Keeling et al , ), although some suggest beginning with a higher target INR (Cohen et al , ).…”
Section: Arterial Thrombosismentioning
confidence: 99%